THE PREVALENCE OF EFFECTIVENESS OF BOLUS DOSE OF I/V HYDRALAZINE VERSUS I/V LABETALOL FOR THE EARLIER CONTROL OF BLOOD PRESSURE IN SEVERE PREECLAMPTIC PATIENT: A COMPARATIVE STUDY - KUMARI, S; DARS, S; ZAHRA, SS; PAWAN, N; AHMED, R (Biological and Clinical Sciences Research Journal, 2022)
To compare the efficacy of hydralazine and labetalol for the management of blood pressure in patients with severe preeclampsia to improve maternal and fetal outcomes. 6 months from March 2022 to September 2022 in the Department of obstetrics and gynecology, Liaquat University Hospital, Hyderabad and Razia Iqbal Hospital Multan, a Cross-sectional study was carried out. The study was conducted on 57 women diagnosed with severe preeclampsia. The subjects were divided into two groups. Group A was administrated I/V hydralazine bolus doses of 5 mg over 2 minutes with an interval of 20 minutes. Group B was administered I/V labetalol bolus doses of 20mg over 2 minutes at an interval of 10 minutes. The average age of the patients was 25.58±3.89 years. The efficacy of bolus dose of hydralazine (82.1%) and labetalol (75.9%) was statistically insignificant (p=0.56). The average time was 52 minutes the total hydralazine was 12.25 mg, in the case of the labetalol group the average time was 18.62 minutes, and the total dose was 68.28 mg. Both hydralazine and labetalol have similar efficacy as antihypertensive medications and can be used to treat hypertensive disorders in pregnant women.